If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 3n + 5 + -6 Reorder the terms: 17 = 5 + -6 + 3n Combine like terms: 5 + -6 = -1 17 = -1 + 3n Solving 17 = -1 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 17 + -3n = -1 + 3n + -3n Combine like terms: 3n + -3n = 0 17 + -3n = -1 + 0 17 + -3n = -1 Add '-17' to each side of the equation. 17 + -17 + -3n = -1 + -17 Combine like terms: 17 + -17 = 0 0 + -3n = -1 + -17 -3n = -1 + -17 Combine like terms: -1 + -17 = -18 -3n = -18 Divide each side by '-3'. n = 6 Simplifying n = 6
| 3x+3-50=201 | | f(x+4)=4(x+4)-8 | | 3x+3=201 | | 5(24-b)=7b | | t=75*500*5 | | 19x+12x+4+20y-8=180 | | 6k-k-8= | | H=4w-40 | | 2.4c-2=0.4(1+3k) | | 11(x+3)-3x=4(2x+4)-20 | | 3+4+5x+2=3+2x | | 33x+20y-176=0 | | 11z-3=z-13 | | 6x+18=-2x+30 | | 1/3x-1/5x2 | | x/11=x/5-6 | | 332-41x-124=3-41x+22 | | 5(a-1)=2(a-4)-6 | | f(5)=4(5)-8 | | -22-8x=-8(x+5)-3x | | -5(4x-3)+1=-20x+16 | | 19+3r-5=-(31+6r) | | 21t-52-312t-72=12-513t+12 | | 3(2x-5)-4x=6x+1 | | 2(3a-4)=8a-11 | | h(x)=5x-7 | | 3x+2=3(x-4) | | 3x+9=3(x-1) | | 3(2x+1)-x=8-4x+6 | | 2(-3x+5)+7x=18-7x | | 6n+2n=11 | | Q+6.4=9.3 |